Ultrastructural response of the retinal cells and neurovascular unit to neuroinflammation induced by lipopolysaccharide - Bilin Rao; Xiaotian Wu; Xiaoqing Liu; Fenglan Wang; Fang He; Xin Lin; Guiyu Guan; Xiaoqian Lai; Jun Zhang (Brain Structure and Function, 2026)

Distinct cellular localization of α- synuclein and β-synuclein in the chick retina - Fang He; Lin Liu; Shaoxuan Wang; Xin Lin; Guiyu Guan; Xiaoqian Lai; Xi Yu; Xiaotian Wu; Zhihao Shen; Bilin Rao; Mei-Ling Gao; Xuejiao Chen; et al. (Brain Structure and Function, 2025)

Beyond tractography in brain connectivity mapping with dMRI morphometry and functional networks - Jui-To Wang; Ching-Po Lin; Huei-Min Liu; Carlo Pierpaoli; Chun-Yi Zac Lo (Brain Structure and Function, 2025)
Traditional brain connectivity studies have focused mainly on structural connectivity, often relying on tractography with diffusion MRI (dMRI) to reconstruct white matter pathways. In parallel, studies of functional connectivity have examined correlations in brain activity using fMRI. However, emerging methodologies are advancing our understanding of brain networks. Here we explore advanced connectivity approaches beyond conventional tractography, focusing on dMRI morphometry and the integration of structural and functional connectivity analysis. dMRI morphometry enables quantitative assessment of white matter pathway volumes through statistical comparison with normative populations, while functional connectivity reveals network organization that is not restricted to direct anatomical connections. More recently, approaches that combine diffusion tensor imaging (DTI) with functional correlation tensor (FCT) analysis have been introduced, and these complementary methods provide new perspectives into brain structure–function relationships. Together, such approaches have important implications for neurodevelopmental and neurological disorders as well as brain plasticity. The integration of these methods with artificial intelligence techniques have the potential to support both basic neuroscience research and clinical applications.

Microglia heterogeneity during neuroinflammation and neurodegeneration in the mouse retina - Bilin Rao; Xiaoqing Liu; Jiayi Xiao; Xiaotian Wu; Fang He; Qingwen Yang; Wenna Zhao; Xin Lin; Jun Zhang (Brain Structure and Function, 2024)

Cell-specific localization of β-synuclein in the mouse retina - Wenhui Zhong; Qingwen Yang; Fenglan Wang; Xin Lin; Zhongqun Chen; Jing Xue; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Jun Zhang (Brain Structure and Function, 2024)

Distribution and synaptic organization of substance P-like immunoreactive neurons in the mouse retina - Fenglan Wang; Wenhui Zhong; Qingwen Yang; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Xin Lin; Jun Zhang (Brain Structure and Function, 2023)

Postnatal development of BAG3 expression in mouse cerebral cortex and hippocampus - Xinlu Li; Geng Lin; Tongtong Liu; Ning Zhao; He Xu; Huaqin Wang; Wei Zheng (Brain Structure and Function, 2021)

AII amacrine cells: quantitative reconstruction and morphometric analysis of electrophysiologically identified cells in live rat retinal slices imaged with multi-photon excitation microscopy - Bas-Jan Zandt; Jian Hao Liu; Margaret Lin Veruki; Espen Hartveit (Brain Structure and Function, 2017)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)